Draft genome sequence of a Chitinophaga strain isolated from a Lignocellulose biomass-degrading consortium - Kishi, Luciano T. [UNESP]; Lopes, Erica M. [UNESP]; Fernandes, Camila C. [UNESP]; Fernandes, Gabriela C. [UNESP]; Sacco, Lais P. [UNESP]; Carareto Alves, Lucia M. [UNESP]; Lemos, Eliana G.M. [UNESP] (American Society for Microbiology, 2017)
Chitinophaga comprises microorganisms capable of degrading plantderived carbohydrates, serving as a source of new tools for the characterization and degradation of plant biomass. Here, we report the draft genome assembly of a Chitinophaga strain with 8.2 Mbp and 7,173 open reading frames (ORFs), isolated from a bacterial consortium that is able to degrade lignocellulose.